Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve for [tex]\( x \)[/tex]:

[tex]\[ | |x - 1| - 2 | = | x - 3 | \][/tex]


Sagot :

Sure, let's solve the equation [tex]\(| |x-1| - 2 | = |x - 3|\)[/tex] step-by-step.

### Step 1: Understanding Absolute Values

The equation involves absolute values, which means we need to consider the different cases where the expressions inside the absolute values change from positive to negative and vice versa.

### Step 2: Analyze Inner Absolute Value

First, let’s break down the inner absolute portions individually:

1. [tex]\(|x - 1| - 2\)[/tex]
2. [tex]\(|x - 3|\)[/tex]

We need to consider different scenarios for [tex]\(x\)[/tex] that affect these expressions:

1. [tex]\(x - 1 \geq 0\)[/tex] : [tex]\(x \geq 1\)[/tex]
2. [tex]\(x - 1 < 0\)[/tex] : [tex]\(x < 1\)[/tex]
3. [tex]\(x - 3 \geq 0\)[/tex] : [tex]\(x \geq 3\)[/tex]
4. [tex]\(x - 3 < 0\)[/tex] : [tex]\(x < 3\)[/tex]

### Step 3: Break Down the Cases

We'll evaluate the absolute value equation in piecewise sections based on these intervals. Here we will include necessary intervals:

#### Case 1: [tex]\(x \geq 3\)[/tex]

For [tex]\(x \geq 3\)[/tex]:
- [tex]\(|x - 1| = x - 1\)[/tex] since [tex]\(x - 1 \geq 0\)[/tex]
- So, [tex]\(|x - 1| - 2 = (x - 1) - 2 = x - 3\)[/tex]
- Also, [tex]\(|x - 3| = x - 3\)[/tex]

The equation becomes:
[tex]\[|x - 3| = |x - 3|\][/tex]

This is true for all [tex]\(x \geq 3\)[/tex]. Thus, all points in this interval satisfy the equation. Hence, one solution set is:
[tex]\[x \geq 3\][/tex]

#### Case 2: [tex]\(1 \leq x < 3\)[/tex]

For [tex]\(1 \leq x < 3\)[/tex]:
- [tex]\(|x - 1| = x - 1\)[/tex] since [tex]\(x - 1 \geq 0\)[/tex]
- So, [tex]\(|x - 1| - 2 = (x - 1) - 2 = x - 3\)[/tex]
- Also, [tex]\(|x - 3| = 3 - x\)[/tex] since [tex]\(x - 3 < 0\)[/tex]

The equation becomes:
[tex]\[|x - 3| = |3 - x|\][/tex]

Specifically:
[tex]\[|x - 3| = 3 - x = x - 3\][/tex]

If we solve this:
[tex]\[3 - x = x - 3\][/tex]
[tex]\[3 + 3 = x + x\][/tex]
[tex]\[6 = 2x\][/tex]
[tex]\[x = 3\][/tex]

This [tex]\(x = 3\)[/tex] falls under both intervals 1 ≤ x < 3, therefore this solution also holds. Therefore, another solution is:
[tex]\[x = 3\][/tex]

(Note that since [tex]\(3 \geq 3\)[/tex], this overlaps with the previous solution).

#### Case 3: [tex]\(x < 1\)[/tex]

For [tex]\(x < 1\)[/tex]:
- [tex]\(|x - 1| = 1 - x\)[/tex] since [tex]\(x - 1 < 0\)[/tex]
- So, [tex]\(|x - 1| - 2 = (1 - x) - 2 = -x - 1\)[/tex]
- [tex]\(|x - 3| = 3 - x\)[/tex] since [tex]\(x - 3 < 0\)[/tex]

The equation becomes:
[tex]\[|- x - 1| = |3 - x|\][/tex]

Specifically:
[tex]\[-(x + 1) = 3 - x\][/tex]

Solving this:
[tex]\[- (x + 1) = 3 - x\][/tex]
[tex]\[-x - 1 = 3 - x\][/tex]

This doesn't cancel out except for extraneous [tex]\(x\)[/tex]. Therefore, no valid [tex]\(x\)[/tex] is extracted.

### Final Answer

The solutions for the equation are:
[tex]\[x \geq 3.\][/tex]

Upon consolidating the acceptable ranges, we can conclude that [tex]\(x \geq 3\)[/tex]. Therefore, the full set of solutions for the equation [tex]\(||x-1|-2|=|x-3|\)[/tex] is [tex]\(x \geq 3\)[/tex], uncommon for complex algebraic absolute scenarios.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.